2015
DOI: 10.1111/jcmm.12711
|View full text |Cite
|
Sign up to set email alerts
|

In vitro morphology, viability and cytokine secretion of uterine telocyte‐activated mouse peritoneal macrophages

Abstract: Telocytes (TCs), a distinct interstitial cell population, have been identified in the uterus, oviduct and placenta, with multiple proposed potential biological functions. Their unique structure allows them to form intercellular junctions with various immunocytes, both in normal and diseased tissues, suggesting a potential functional relationship with the local immune response. It has been hypothesized that through direct heterocellular junctions or indirect paracrine effects, TCs influence the activity of loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 96 publications
(211 reference statements)
1
36
0
Order By: Relevance
“…The interalveolar region contained predominantly CD34‐positive cells on P30, with the formation of networks that separate the clusters of alveoli from each other and separate clusters of alveoli from the periurethral smooth muscle, thus attributing to the exclusively CD34‐positive interstitial cells uniquely a role of ICCs progenitor cells is a limited proposition, in view of the evidence that these cells possess many other functions in the tissue organisation and functionality in various organs 8, 10, 11, 12, 17, 18, 24, 25. CD34‐positive telocytes that do not express c‐Kit may also perform a pacemaker function 48, 49 via c‐Kit‐independent pathways, such as the SK3 pathway, by inhibiting electrical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interalveolar region contained predominantly CD34‐positive cells on P30, with the formation of networks that separate the clusters of alveoli from each other and separate clusters of alveoli from the periurethral smooth muscle, thus attributing to the exclusively CD34‐positive interstitial cells uniquely a role of ICCs progenitor cells is a limited proposition, in view of the evidence that these cells possess many other functions in the tissue organisation and functionality in various organs 8, 10, 11, 12, 17, 18, 24, 25. CD34‐positive telocytes that do not express c‐Kit may also perform a pacemaker function 48, 49 via c‐Kit‐independent pathways, such as the SK3 pathway, by inhibiting electrical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Telocytes may also exercise pacemaker function by means of the c‐Kit, but may also possess a supportive function for the contraction of periductal smooth muscle, possibly by means of c‐kit‐independent pathways, such as via the SK3 (small conductance calcium‐activated potassium Channel 3) pathway 20, 23. The function of telocytes varies between organs 8, 10, 11, 12, 17, 18, 24, 25, and their role in the prostate remains elusive, in addition to lack of information regarding the development of these cells in prostate tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Growth factors, including IL-6, VEGF, macrophage inflammatory protein 1a, macrophage inflammatory protein-2 and monocyte chemoattractant protein 1, are significantly expressed along with additional cytokines, including IL-2, IL-10, IL-13 and chemokines, such as growthrelated oncogene/keratinocyte-derived chemokine in the secretome of cultured rodent cardiac TCs [17]. Besides, in a renal ischaemia-inflammatory injury model, TCs activated the nuclear factor kappa B signalling pathway and upregulated the mRNA levels of pro-inflammatory cytokines such as IL-1 and tumour necrosis factor-a [17,18]. 1 Nanocontacts-heterocellular communications between TCs and cardiomyocytes, which do not belong to classic types of junctions found in textbooks.…”
Section: Characteristics Of Telocytes (Morphology Contacts)mentioning
confidence: 99%
“…Presumably, this support might contribute to tissue homeostasis, regeneration or repair and transmission of intercellular signals . Ultrastructural evidence showed that telocytes were spatially close not only to capillaries, nerve fibres, myocytes, smooth muscle cells and stem cells but also to macrophages, mast cells, eosinophils and lymphocytes . Telocytes might modulate the immunocytes through direct synapse‐like contact or indirect paracrine communication by secreting soluble mediators, such as IL‐6, VEGF and nitric oxide .…”
Section: Introductionmentioning
confidence: 99%